Effectiveness and acceptability of a text message intervention (DTEXT) on HbA1c and self-management for people with type 2 diabetes. A randomized controlled trial. Issue 7 (July 2021) - Waller, Karen; Furber, Susan; Bauman, Adrian; Allman-Farinelli, Margaret; van den Dolder, Paul; Hayes, Alison; Facci, Franca; Franco, Lisa; Webb, Alison; Moses, Robert; Cook, Rebecca; Gugusheff, Jessica; et al.
Highlights: DTEXT is the largest Australian RCT for type 2 diabetes text message health interventions Text message interventions are highly accepted amongst people with type 2 diabetes A type 2 diabetes text message intervention can improve some nutritional outcomes DTEXT offers feasible self-management support to complement existing diabetes care Abstract: Objective: Determine the effectiveness and acceptability of a text message intervention (DTEXT) on HbA1c and self-management behaviors for Australian adults with type 2 diabetes. Methods: Using intention to treat analysis and generalized estimating equations, this randomized controlled trial of 395 adults determined change in HbA1c at 3 and 6 months between the intervention and control group. Secondary outcomes included change in nutrition, physical activity, blood lipid profile, body mass index, quality of life, self-efficacy, medication taking and program acceptability. Results: No significant difference was observed between the intervention or control group for HbA1c at 3 months ( P = 0.23) or 6 months ( P = 0.22). Significant improvements were seen in consumption of vegetables at 3 months ( P < 0.001) and 6 months ( P = 0.04); fruit at 3 months ( P = 0.046) and discretionary sweet foods at 3 months ( P = 0.02). No other significant effects seen. The intervention demonstrated high rates of acceptability (94.0%) and minimal withdrawal (1.5%). Conclusions: DTEXT was an acceptable text message intervention that improved some nutritional behaviors in people with type 2 diabetes, but did not significantly improve HbA1c or other outcomes. Further research is required to optimize DTEXT. Practice implications: DTEXT provides an acceptable, feasible form of self-management support that may complement existing diabetes care.